Bigger is not Necessarily Better: An Analysis of Violence Against Women Estimates from the National Crime Victimization Survey and the National Violence Against Women Survey - Rand, Michael R. (Journal of quantitative criminology, 2005)
Apparent differences between violence against women estimates from the National Crime Victimization Survey (NCVS) and the National Violence Against Women Survey (NVAWS) continue to generate confusion. How is it that two surveys purporting to measure the nature and extent of violence against women present such seemingly dissimilar estimates? The answer is found in the important, yet often over-looked details of each survey. Our objective is to clarify some of the reasons for apparent disparities between NCVS and NVAWS estimates by first identifying why published estimates are not comparable. Next, we adjust NCVS estimates to make them comparable to NVAWS estimates by restricting NCVS estimates to 1995 and including only persons age 18 or older, and by applying the NVAWS series victimization counting protocol to NCVS estimates. Contrary to findings in the literature, the NVAWS did not produce statistically greater estimates of violence against women compared to the NCVS. Further, incident counting protocols used in the NVAWS and the recalibrated NCVS increased the error, and decreased the reliability of the estimates.